Aloe vera gel, an excellent base material for edible films and coatings. (October 2021) - Maan, Abid Aslam; Reiad Ahmed, Zienab Fawzy; Iqbal Khan, Muhammad Kashif; Riaz, Asad; Nazir, Akmal
Abstract: Background: Edible films/coatings are thin layers of eatable materials which, when applied to foods, can modify the exchange of molecules between food and environment as well as between different compartments of the same food. The films/coatings help the foods to maintain their freshness and also facilitate in their transportation, storage and display. As demand for healthy foods is increasing rapidly, various novel materials from herbal sources are extensively being explored as raw materials for edible films/coatings. Scope and approach: Aloe vera is a popular herbal plant and is well known for its therapeutic properties. The gel extracted from Aloe vera leaves comprises of a variety of bioactive compounds, minerals and phenolic contents. For this reason, Aloe vera gel has attracted considerable attention as edible and active film/coating material. The present paper provides a detailed literature review on extraction, suitability and applications of Aloe vera gel as edible film/coating material, either alone and in combination with conventional film forming materials. Key findings and conclusions: Aloe vera gel films/coating are quite effective for shelf-life extension of various perishable food commodities (in a dose-dependent manner); however, the optimum gel concentration still needs to be investigated. The blending of Aloe vera gel with traditional biopolymers (proteins and polysaccharides) and lipids (emulsions) seems a promising approach for tuning properties of films/coating in terms of transparency, smoothness, rigidity, elasticity, water vapor permeability, and bio-functionality. Further research is needed to address some technological challenges to develop Aloe vera gel-based films/coatings with easily tunable properties. Graphical abstract: Image 1 Highlights: Aloe vera gel-based films/coatings represent biodegradable and active food packaging. Blending Aloe vera gel with biopolymers improves functionality of coatings/films. Aloe vera gel-based films/coatings with easily tunable properties are still needed.